Dimensioning and tolerancing handbook - Drake, Paul J. (McGraw-Hill's AccessEngineering., 1999)
This book tries to capture the major topics that fall under the umbrella of "Variation Management." The book is laid out so that the reader can easily understand the variation management process and how each chapter maps to this process. This book has two purposes. It is a "one-step" resource for people who want to know everything about dimensional management and variation management. It is a useful reference for specific target audiences within the variation management process. This book includes many new techniques, methodologies, and examples that have never been published before. Much of the new material revolves around Six Sigma techniques that have evolved within the past 5 years. This book offers high level information and expertise to a broad spectrum of readers, while providing detailed information for those needing specific information. The contributors are practitioners who have hands-on experience. Much of the expertise in this book is a result of identifying needs to solve problems in our companies and businesses. Many of the chapters are the documented solutions to these needs.